Cars, Space, and the Dynamics of Power in Cuéntame cómo pasó ('Tell Me How It Happened') - Linda B. Bartlett (Studies in 20th & 21st Century Literature, 2017)
Cuéntame cómo pasó 'Tell Me How It Happened,' Radio Televisión Española’s long-running television series, recreates Spain’s recent past from the late years of the Franco regime through the transition to democracy and beyond through the daily experiences of the fictional yet typical Alcántara family, thus functioning as a form of historical memory project. This critically-acclaimed program, which debuted in fall 2001, has attracted not only record-size audiences in its 18 seasons (to date), but also scholarly interest as well. While other studies have analyzed the use of the television medium to represent history, or critiqued its historical accuracy, the present article utilizes spatial theory to examine the geography of change portrayed in the program. Informed by the work of theorists such as Nancy Duncan and Doreen Massey, this study specifically considers how increased automobility, the ability to traverse space rapidly and independently, is a sign of growing individual and national autonomy in a society emerging from authoritarianism. The study of the relationship between space and power, which takes into account both class and gender, reveals the equivocal nature of Spain’s advances in the post-Franco era.
Keywords: Spain; television; history; geography; space; power; class; gender; automobility